Surface Characterization and Corrosion Behavior of 90/10 Copper-Nickel Alloy in Marine Environment - Jin, Tingzhu (Materials (Basel), 2019)
Surface characterization and corrosion behavior of 90/10 copper-nickel alloy in seawater from Xiamen bay at 30 °C for 56 days were investigated in this study. The results indicated that the corrosion product layer was mainly a mixture of CuO, Cu(2)O, and Cu(OH)(2), with a transition to CuCl, CuCl(2), and Cu(2)(OH)(3)Cl during the corrosion process. However, as corrosion proceeds, the resistance of the product film was reduced due to its heterogeneous and fairly porous structures, which led to local corrosion of the alloy. The corrosion potentials (E(corr)) increase while corrosion current densities (I(corr)) decrease with time because of the formation of protective oxide film.